Improving Early Childhood Emotional Regulation through Colored Light Games: A Play-Based Intervention Approach - Yolanda Pahrul; Adinda Salsabila Rosandi (AL-ISHLAH: Jurnal Pendidikan, 2026)
Emotion regulation in early childhood (ages 4–6) is still developing and often manifests in emotional outbursts and difficulty following classroom instructions. This study investigates the effectiveness of the Lampu Warna (Color Lights) game, a structured play-based learning strategy, in improving children’s emotion regulation.A pretest–posttest control-group design was employed with 32 kindergarten children in Pariaman Regency, West Sumatra, randomly assigned to an experimental group (n = 16) and a control group (n = 16). The intervention consisted of eight sessions (15–20 minutes each), conducted twice weekly over four weeks during circle time. Emotion regulation was measured using the teacher-rated Emotion Regulation Checklist (ERC). Data were analyzed using Wilcoxon signed-rank and Mann–Whitney U tests in JASP (version 19).The experimental group showed a substantial improvement in emotion regulation, with mean scores increasing from 47.88 to 71.06 (W = 0.00; z = −3.516; p 0.001; r = 0.88). The control group exhibited no significant change. Between-group analysis confirmed significantly higher outcomes in the experimental group (U = 256.0; p 0.001; Cliff’s δ = 1.00).The findings indicate that the Lampu Warna game effectively enhances emotion regulation by engaging children in structured, interactive play that supports emotional awareness and control.The Lampu Warna game is an effective play-based intervention for improving emotion regulation in early childhood and offers practical implications for classroom-based socio-emotional learning strategies.